Howzat! Expert umpires use a gaze anchor to overcome the processing demands of leg before wicket decisions. Issue 17 (2nd September 2021) - Ramachandran, Pravinath; Watts, Matt; Jackson, Robin C.; Hayes, Spencer J.; Causer, Joe
ABSTRACT: Cricket umpires are required to make high-pressure, match-changing decisions based on multiple complex information sources under severe temporal constraints. The aim of this study was to examine the decision-making and perceptual-cognitive differences between expert and novice cricket umpires when judging leg before wicket (LBW) decisions. Twelve expert umpires and 19 novice umpires were fitted with an eye-tracker before viewing video-based LBW appeals. Dependent variables were radial error (cm), number of fixations, average fixation duration (ms), final fixation duration (ms), and final fixation location (%). Expert umpires were significantly more accurate at adjudicating on all aspects of the LBW law, compared to the novice umpires (p < .05). The expert umpires' final fixation prior to ball-pad contact was directed significantly more towards the stumps (p < .05), whereas the novice umpires directed their final fixation significantly more towards a good length (p < .05). These data suggest that expert umpires utilize specialized perceptual-cognitive skills, consisting of a gaze anchor on the stumps in order to overcome the processing demands of the task. These data have implications for the training of current and aspiring umpires in order to enhance the accuracy of LBW decision-making across all levels of the cricketing pyramid.